1966
DOI: 10.1128/jb.91.2.578-582.1966
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Oxidation of Orthophosphite

Abstract: A variety of bacteria grown on a glucose and salts medium were capable of utilizing orthophosphite as a sole source of phosphorus. Two organisms, Pseudomonas fluorescens 195 and Serratia marcescens 24, were studied in detail. Growth rates and total cell yields of the bacteria grown on phosphite indicated that the bacteria utilized phosphite as efficiently as phosphate. The ability to oxidize the anion was shown to be inducible. A period of adaptation was required prior to growth on phosphite when phosphate-gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…Decreases in hypophosphite or phosphite concentration were usually accompanied by little or no phosphate accumulation in the culture medium. This is consistent with work reported by others (3,9) and indicates that the utilized phosphorus is being incorporated into organic compounds within the cell. This hypothesis was further verified by the work with 32P-labeled hypophosphite in which intermediate organic compounds containing labeled phosphate were isolated.…”
Section: Discussionsupporting
confidence: 92%
“…Decreases in hypophosphite or phosphite concentration were usually accompanied by little or no phosphate accumulation in the culture medium. This is consistent with work reported by others (3,9) and indicates that the utilized phosphorus is being incorporated into organic compounds within the cell. This hypothesis was further verified by the work with 32P-labeled hypophosphite in which intermediate organic compounds containing labeled phosphate were isolated.…”
Section: Discussionsupporting
confidence: 92%
“…Systematic studies on the suitability of phosphite as P fertilizer were initiated in the early 1950s indicating that higher doses of phosphite impaired plant growth in the first year, while plant growth was improved in subsequent years (MacIntire et al, 1950). Indeed, over several decades it was supposed that the P fertilisation effect is indirectly mediated via oxidation to phosphate by soil microbes and within plant tissues (Adams and Conrad, 1953;Casida, 1960;Malacinski and Konetzka, 1966;, and the molecular and genetic characterisation of such a biochemical pathway has been reported by Metcalf and Wolfe (1998). The interest in phosphite as a P source was renewed when Lovatt (1990a, b) reported that phosphite could not only restore growth of P-deficient citrus and summer squash (Cucurbita pepo L.), but also induced higher flower and fruit set (Lovatt, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations have shown that biologically catalyzed oxidation of reduced P compounds can occur. A number of bacteria have been shown to be capable of oxidizing reduced P compounds when these are provided as the sole source of P. Inorganic phosphite (ϩ3 valence) was oxidized to phosphate by numerous laboratory strains of microorganisms, including prokaryotes such as Escherichia coli, Agrobacterium tumefaciens, and several species of Pseudomonas and Rhizobium, as well as one eukaryote, Saccharomyces cerevisiae (1,6,26). Hypophosphite (ϩ1 valence) can also be oxidized to phosphate by bacteria (9,16).…”
mentioning
confidence: 99%